SFRP1, Posible biomarcador en la progresión o regresión de lesiones de cérvix asociado al Virus del Papiloma Humano - Juvenal Darío Baena-Acevedo (Asociación Colombiana de Infectología, 2021)
Objective. The aim of this work was to compare the expression of mRNA and proteins of SFRP1, PTPRN, CDO1, EDNRB, CDX2, EPB41L3 and HAND1 in patients with low and high grade cervical intraepithelial lesion, with subsequent progression or regression. Material and Methods: Gene expression analysis was conducted through RT-PCR and protein expression analysis was performed by immunohistochemistry. The statistics analysis were Wilcoxon test, Spearman's correlation coefficient and concordance index. The samples were paired during moment 1 (initial patient diag-nosis) and moment 2 (follow-up histological diagnosis). Results: SFRP1 showed a trend of higher mRNA expression in low-grade intra-epithelial lesions (moment 2) Vs. high-grade (moment 1). The expression of proteins by immunohistochemistry of SFRP1 in progression cases (83.3%) showed a decrease in its graduation (p = 0.0313*); the other genes under study had no statistically significant. Discussion: SFRP1 showed a biological behavior adjusted to the results of previous studies where hypermethylation was found in high-grade intra-epithelial lesions; its subexpression by hypermethylation has been reported in other cancers, a process that collaborates with its silencing and epithelial-mesenchymal tran-sition of cervical. Conclusions. SFRP1 is a potential biomarker in preneoplastic lesions of the cervix associated with human papillomavirus.